Energy Harvesting from a Portal Frame with a Shape Memory Alloy - Tusset, Angelo Marcelo; Pires, Dim; Lenzi, Giane G.; Iliuk, Itamar; Rocha, Rodrigo T.; Balthazar, José Manoel [UNESP] (Springer Nature, 2024)
In this work, the investigation of energy harvesting for a portal frame structure is presented. A Shape Memory Alloy (SMA) and a piezoelectric material are coupled to the portal frame. The structure is excited by a non-ideal DC motor of limited power supply attached to its rigid body. The energy harvesting is carried through the piezoelectric material, which is mathematically represented by a nonlinear electromechanical coupling model. The behavior of the SMA is described by a system of differential equations that consider the martensite fraction and the temperature as the state variables thermodynamically constrained to the mechanical ones. Numerical results demonstrate the significant influence of both piezoelectric material and Shape Memory Alloy in the behavior of the system and energy harvesting. In addition, it is highlighted that the use of the SMA makes the vibrations of the structure possible to be controlled. In addition, for specific values of the elastic stiffness of Shape Memory Alloy, the harvested energy is increased.
Keywords: Nonideal systems; Nonlinear dynamics; Piezoelectric devices